Spatial and spatiotemporal pattern formation in generalised turing systems - Maini, P (1996)
Reaction-diffusion, or Turing, models have been proposed to account for a number of pattern formation phenomena in early development. However, there are a number of crucial morphogenetic phenomena that contradict the standard Turing model. Here we review three generalisations of the Turing model and show how they can be applied to two such phenomena. We discuss how these generalisations can provide insight to the processes underlying patterning in these cases.